Brain metastases in lung cancer - Smrdel, Uroš (Radiology and oncology (Ljubljana), 2003)
Background. Brain metastases are common patterns of dissemination in lung cancer patients. In this paper we would like to assess the pattern of brain metastases in lung cancer patients and the impact of prognostic factors on thesurvival of lung cancer patients with brain metastases. Patients and methods. In the year 1998 there were 974 registered patients with lung cancer in Slovenia, six hundred and fifteen of them were treated at the Institute of Oncology Ljubljana and we analyzed them. Among 615 patients 137 (22.3%) of them have had brain metastases during a natural course of disease. Results. For 12 patients presenting with solitary brain metastases (most of them were undertaken metastaseetomy) median survival was 7.6 months, while in patients with multiple brain metastases the median survival was 2.8 months (p = 0.0018). Of the 137 patients 45 (32.8%) were small cell lung cancer patients, 43 (31.4%) were adenocarcinoma patients and 19 (13.9%) were squamous cell carcinoma patients. Patients with performance status (WHO scale) less than 2 had the median survival time 3.7 months while patients with performance status2 or more had median survival time 2.7 moths (p=0.0448). Conclusions. Patients with solitary brain metastases had better survival comparing with those who had multiple metastases. It is surprisingly that the portion of brain metastases patients with adenocarcinoma is almost equal to those with small-call lung cancer therefore, the prophylactic cranial radiation becomes actual for both groups of patients. The performance status of patients with brain metastases remains very important prognostic factor.
Keywords: Brain Neoplasms; Lung Neoplasms; metastaze; možgani; Možganske novotvorbe; Neoplasm Metastasis; Novotvorba, metastaza; Pljučne novotvorbe; pljučni rak; Preživetje, analiza; prognoza; Secondary; Survival Analysis